Effects of biostimulants on germination, agronomic performance, and nutritional quality of Pakchoi (Brassica rapa L. subsp. chinensis) cultivars in organic cultivation - Ibrahim, Illani Zuraihah (2025)
Organic farming is increasingly recognized as a sustainable alternative to conventional agriculture, offering significant environmental benefits, enhancing soil health, and supporting long-term ecosystem resilience. However, organic production often faces inherent challenges, including lower yields and reduced crop size, primarily due to limited nutrient availability, the absence of synthetic growth enhancers, and natural pest pressures. While biostimulants have emerged as promising tools to improve plant productivity in an eco-friendly manner, their application within organic systems remains underexplored, particularly concerning their effects on crop physiology, phytochemical attributes, and soil fertility.